Preventive Exploration of Conflicts on Christmas Celebration at Schools - SYAR’I, A. (Utopía y Praxis Latinoamericana, 2020)
SUMMARY Some Muslim teachers are present during the Christmas celebration at the public middle school in Pangkalan Bun, Central Kalimantan and are even engaged in wishing "Merry Christmas"; but many others do not attend the rituals of celebration or are able to wish "Merry Christmas". That is to say, the religious diversity in the school in question, leads to celebrate Christmas in a plural way and according to the opinion of the six religions that coexist in the educational campus. All Muslim teachers are selective about the halal or haram foods and drinks served during the celebrations; some also do not participate in worship activities during the celebration. Muslims and non-muslims already understood each teacher’s attitudes and views and gave each other opportunities according to religion and beliefs. RESUMEN Algunos maestros musulmanes estan presentes durante la celebración de Navidad en la escuela publica media en Pangkalan Bun, Central Kalimantan y hasta se dedican a desear "feliz Navidad"; pero otros tantos no asisten a los rituales de celebración ni son capaces de desear "feliz Navidad". Es decir, la diversidad religiosa en la escuela en cuestión, conlleva a celebrar la Navidad de manera plural y atendiendo al dictamen de las seis religiones con las que se convive en el recinto educativo. Todos los maestros musulmanes son selectivos acerca de las comidas y bebidas halal o haram que se sirven durante las celebraciones; además algunos tampoco participan en actividades de adoración durante la celebración. Musulmanes y no musulmanes ya entendieron las actitudes y puntos de vista de cada maestro y se dieron oportunidades mutuamente de acuerdo con la religión y las creencias.